Usage of Multiple Clouds to increase Security in Cloud Computing - Kumar, Ch. Anjani; Rao, K. Subba (International Journal of Computer Sciences and Engineering, 2014)
In today’s world Cloud computing has emerged like as a new model of computing. It is a paradigm shift in the computing history. Cloud services are ready to available without capital investment as they are commoditized. Cloud users may get services in pay per use fashion and enjoy so many benefits of cloud computing including less cost and accessibility from anywhere in the world. However, users have security issues as they outsource their secret business data to cloud and treat the cloud as “untrusted”. By using a single cloud service provider there might be the risk of service availability, possibility of failure and insider theft of data. By Moving towards multi clouds can address security problems. This paper aims of investigating how multiple-cloud can increase security and have impact on the usage of the cloud computing usage technology. We built a prototype application to simulate the advantages of using multiple-clouds to increase security. The empirical result shows that multiple-clouds can increase security.